MODEL PENENTUAN NILAI LAHAN PADA SULTANAAT GROND (SG) DAN PAKUALAMANAAT GROND (PAG) DI DAERAH ISTIMEWA YOGYAKARTA - , EKO SUHARTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sultanaat Grond (SG) and Pakualamanaat Grond (PAG) is land owned by the Kraton Yogyakarta and Kadipaten Paku Alaman. Because of their uniqueness, SG and PAG land values do not follow the land market in general and there is no reference standard to determine as on private lands. The aims of this study were : 1) design structural model determining the value of land in SG land and PAG by using Structural Equation Model (SEM) - SmartPLS, 2) determine the influencing factors that affect the land value of SG and PAG, and 3) examine spatial distribution of land value of SG and PAG land in Yogyakarta Special Region. This study used spatial approach and statistical analysis. Sampling in this study are 93 lots af SG and PAG land, and 93 people that use those lands, that sampled by multi stage methods. The data analysis used were Structural Equation Model â Partial Least Square (SEM-PLS) and spatial analysis. The research resuls showed that: 1) the structural model of land values of the SG and PAG ini Bantul and Kulonprogo regency was a direct function of government policy and environment variables, and indirect function of location and social variables.